2023
DOI: 10.1371/journal.pone.0289807
|View full text |Cite
|
Sign up to set email alerts
|

Close-range photogrammetry reveals morphometric changes on replicative ground stones

Giusi Sorrentino,
Fabio Menna,
Fabio Remondino
et al.

Abstract: The pursuit of a quantitative approach to functional analysis of stone tools is an ongoing endeavour for traceologists. Technological advancements in 3D imaging techniques, such as photogrammetry/3D scanners, CT scanning, 3D digital microscopy, confocal microscopy, AFM and FEG-SEM and micro-topographical scanning, have greatly facilitated the detailed capturing of the geometry and surface texture at multiple levels of observation, from the object-scale to the nano-scale. However, while such technological innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The DT showed that even if the stones had the same mechanical parameters, the contact causes more damage on the active tool’s surface than on the passive stone, in very good accordance with the experimental observation, where the maximum extent of depletion was up to −170 μm in the GS17 passive stone and up to −360 μm in the GS18 active stone 35 . In fact, while the phase-field parameter reaches 1 on the GS18 surface (see Fig.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The DT showed that even if the stones had the same mechanical parameters, the contact causes more damage on the active tool’s surface than on the passive stone, in very good accordance with the experimental observation, where the maximum extent of depletion was up to −170 μm in the GS17 passive stone and up to −360 μm in the GS18 active stone 35 . In fact, while the phase-field parameter reaches 1 on the GS18 surface (see Fig.…”
Section: Resultssupporting
confidence: 83%
“…The digital model was created to replicate the damage caused by the replicative use of the stone tools and it has been devised starting from the geometrical data contained in the STL file produced with photogrammetric techniques prior to use, as detailed in 35 and shortly summarised in the Method section. The STL surface mesh of the passive stone GS17 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations